2013
DOI: 10.1002/jnr.23263
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine phosphatase STEP61 negatively regulates amyloid β‐mediated ERK/CREB signaling pathways via α7 nicotinic acetylcholine receptors

Abstract: Striatal-enriched phosphatase 61 (STEP61 ) plays an essential role in synaptic plasticity and has recently been implicated in neurodegenerative disease. Here we characterized a possible role of STEP61 in Alzheimer's disease (AD) pathology using a mouse model of AD (Tg-APPswe/PSEN1dE9, APP/PS1 mice) and an in vitro model of AD [cortical neurons treated with amyloid β (Aβ)1-42 peptides]. Our data indicate age-related elevation of STEP61 levels and the proportion of dephosphorylated STEP61 (active STEP61 ) in wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…4,54 As our results indicated that reduced STEP 61 levels/activity promoted thermal hyperalgesia, we next characterized thermal nociception and STEP 61 levels in the lumbar spinal cord of male and female mice from 3 to 15 months of age. The Hargreaves test showed reduced paw-withdrawal latency with age in males (one-way ANOVA, F (3, 56) = 15.39; P < 0.001; Fig.…”
Section: Resultsmentioning
confidence: 98%
“…4,54 As our results indicated that reduced STEP 61 levels/activity promoted thermal hyperalgesia, we next characterized thermal nociception and STEP 61 levels in the lumbar spinal cord of male and female mice from 3 to 15 months of age. The Hargreaves test showed reduced paw-withdrawal latency with age in males (one-way ANOVA, F (3, 56) = 15.39; P < 0.001; Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Five assays per group. familial model of AD (Xu et al, 2012;Zhang et al, 2013). Furthermore, PTPs may also participate in Ab translocation into lipid rafts.…”
Section: Discussionmentioning
confidence: 97%
“…Aβ 42 induces the altered conformation of FLNA, and altered FLNA enables sustained Aβ 42 signaling via α7nAChR and TLR4, possibly by securing high affinity binding of Aβ [13,15] . Aβ 42 's toxic signaling via α7nAChR activates kinases to hyperphosphorylate tau [25][26][27][28][29][30][31] , leading to its dysfunction and aggregation, and the FLNA-enabled Aβ 42 activation of TLR4 enhances neuroinflammation [13,15] . Moreover, the altered conformation of FLNA is an important catalyst of Aβ toxicities and tau dysfunction, including neuroinflammation and synaptic dysfunction.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive research has elucidated the role of the α7nAChR in the toxicity of soluble Aβ 42 and the consequent hyperphosphorylation of tau [19][20][21][22][23][24] . Soluble Aβ 42 in monomeric or oligomeric form binds and signals via α7nAChR [25][26][27][28] , essentially hijacking this receptor to abnormally activate various kinases [27,[29][30][31] to heighten tau phosphorylation. Supportive data include co-localization of Aβ 42 and α7nAChR in AD pyramidal neurons and a complete blockade of Aβ 42 -induced tau hyperphosphorylation in vitro by α7nAChR antisense oligonucleotides [32] .…”
Section: Aβ Signaling Via α7nachr To Hyperphosphorylate Taumentioning
confidence: 99%